Platelet adhesion and aggregate formation controlled by immobilised and soluble VWF - Schneider, Matthias F.; Fallah, Mohammad A.; Meß, Christian; Obser, Tobias; Schneppenheim, Reinhard; AlexanderKatz, Alfredo; Schneider, Stefan W.; Huck, Volker (BMC molecular and cell biology, 2020)
It has been demonstrated that von Willebrand factor (VWF) mediated platelet-endothelium and platelet-platelet interactions are shear dependent. The VWF’s mobility under dynamic conditions (e.g. flow) is pivotal to platelet adhesion and VWF-mediated aggregate formation in the cascade of VWF-platelet interactions in haemostasis.
Gesehen am 13.10.2025